PERLINDUNGAN HUKUM TERHADAP BURUH ANAK DITINJAU DARI PERSPEKTIF HUKUM PIDANA - Ermanita Permatasari (LPPM STAI DARUSSALAM LAMPUNG, 2014)
The presence of the children who work in places that are categorized as the worst forms of child appropriate for 1982 ILO Convention still be a serious problem and quite significant in this country. Child labor becomes a problematic because in practice the presence of the children there almost resembles the practice of slavery, exploitation of children throughout the day, so practically deprive a child of all their human rights in accordance with the Convention on the Rights of the Child as well as all laws and regulations applicable in the country this. Millions of Indonesian children are now being forced or compelled lost childhood and play them. Economic reasons, most of them forced into underage workers are loaded with risk. Millions of Indonesian children are now stuck in a situation of neglect, the threat of discrimination, exploitation, and violence.